Deterritorialized People in Hyperspace: Creating and Debating Harari Identity over the Internet - Gibb, Camilla (Anthropologica, 2022)
Where Glick-Schiller and others have preferred to use the terms transmigrant or transnational (1992; 1995) rather than immigrant, in order to suggest that identities are multiply constituted and lived across borders, these identities may, in fact, be further complicated by the creation of an additional dimension which others have not considered?a virtual reality within which aspects of community and culture are simultaneously being defined. In the deterritorialized space of hyperspace, where time and space are compressed (cf. Harvey, 1989), and constructions are detached from any local reference (Kearney, 1995: 553), members of a small Ethiopian population, known as the Harari, are invoking a new language of nationhood in order to give shape to a now dispersed community. This is an example of how new media can provide a forum for the creation of national identity outside national borders, and how those with access to this technology are the ones most active in that discussion. This exploration of the use of new media offers insight into the ways in which transnational, and more broadly, transtemporal and transspatial processes are involved in redefining community relations and identities amongst dispersed peoples in a postmodern world.